EVALUASI KINERJA SATUAN POLISI PAMONG PRAJA DI KABUPATEN BANTUL DALAM RANGKA PENEGAKAN PERDA - Sri Handayani (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2020)
The successful implementation of the Government in Bantul Regency in the fields of peace, public order and community protection is under the authority of the Civil Service Police Unit. The research objectives are to evaluate performance achievements, identify factors that affect performance and develop improvements in the implementation of the main duties and functions of the Civil Service Police Unit. This reasearch was descriptive qualitative research with 4 informants as informants consisting of 3 structural officials and 1 lecturer. The results of the study was the achievement of very high performance.it was 103.2% in 2016 and 129.5% in 2017. It shows that the performance was optimal. Performance achievement is supported by the results of the measurement of key indicators (KPI) which include the percentage of completion of violations of order, order and beauty (K3) and the Percentage of enforcement of regional policy. Performance is very high, but violations of regional regulations and local regulations are still many, so that employee distribution activities are needed based on 10 main roads involving 10 civil servants and 20 contract workers.